Research on Mobile Advertising Users' Propagation Ability Evaluation based on the Neutrosophic Cubic Number Multiple-Attribute Decision-Making - Minming Weng; Ying Long (Neutrosophic Sets and Systems)
The evaluation of mobile advertising users' propagation ability assesses how effectively users can share or spread advertisements within their networks. It involves analyzing factors such as user engagement, social influence, sharing frequency, and network reach. By understanding these metrics, advertisers can identify highly influential users who can amplify campaign impact. This process helps optimize targeting strategies, improve ad performance, and maximize return on investment by leveraging users with strong propagation potential in mobile advertising ecosystems. The mobile advertising users' propagation ability evaluation is multiple-attribute decision-making (MADM). In recent years, the MOORA approach has been widely utilized to address multi-attribute decision-making (MADM) problems. To handle the uncertainty inherent in such problems, neutrosophic cubic sets (NCSs) have emerged as a powerful tool for expressing and analyzing uncertain information. This research introduces a novel approach, the neutrosophic cubic number MOORA (NCN-MOORA) approach, to solve MADM problems under the framework of NCSs. Specifically, the approach is applied to evaluate the propagation ability of mobile advertising users, a critical factor in optimizing advertising strategies. To demonstrate the validity of the proposed approach, a numerical case study is conducted. The primary objectives of this research are as follows: (1) to propose the NCN-MOORA approach for solving MADM problems within the NCS environment; (2) to determine attribute weight information using average method, ensuring an unbiased weighting process; (3) to design and apply the NCN-MOORA approach for evaluating mobile advertising users’ propagation ability and compare its performance with existing approaches; and (4) to validate the effectiveness of the proposed approach through comparative analysis. The results confirm that the NCN-MOORA approach offers a reliable and efficient solution for evaluating mobile advertising users’ propagation ability in uncertain environments.